Statistical analysis of intron phase at the splice sites of eukaryotic genes - Jia, Yiyu (2008)
Intron phase is a conserved evolutionary character that refers to the location of introns relative to the three nucleotide positions in a triplet codon. In this report, the distribution of intron phase in eukaryotic genes are discussed. Symmetric exons (exons flanked by symmetrical intron phases) are introduced and their statistical significance in the process of eukaryotic gene evolution are discussed. Some novel concepts, such as "mirror exon set", "compact gene", "exon motif", and "impulse" of exon length distribution are introduced. It is found that introns are significantly biased towards phase 0 introns. A pattern showing an excess of symmetric exons ((0,0), (1,1), (2,2)) is also observed. Our proposed new concept about "mirror exon set" further determines that the intron phase distribution is not random. Significant bias of intron phase zero was observed in both "compact" and "extended" protein coding genes as well. These results could provide insights to exon shuffling that is an evolutionary process to create new genes by shuffling exons.